Alternative possibilities of hyaluronic acid in genitourinary symptoms treatment - A.A. Sukhanova; V.V. Sumenko; R.R. Tkachuk (Publishing House TRILIST, 2021)
Research objective: to evaluate the clinical efficacy of vaginal gel with hyaluronic acid Revitaxa gel in comparison with synthetic estrogen-like topical agent in the treatment of women with genitourinary syndrome, to determine the recurrence rate of atrophic changes as a result of these schemes. Materials and methods. The study included 60 women with genitourinary manifestations and atrophic changes of the vaginal mucosa and cervical epithelium. Clinical, cytological and colposcopic studies were performed to analyze the vaginal epithelium, vaginal microbiocenosis and vaginal tissues. All women with an inflammatory type of smear were prescribed vaginal rehabilitation before the study. Repeated laboratory examination after anti-inflammatory, antibacterial topical therapy confirmed no pathogenic microflora, but signs of atrophy persisted in all women. All women are prescribed local treatment to improve the reparative processes of the vaginal mucosa. The main group (30 women) used Revitaxa gel for local therapy; the control group (30 women) used vaginal suppositories with the synthetic estrogen-like agent promestrienum. Results. Cytological remission after treatment was observed in all women of the control group and in 76.7% of patients in the main group. Restoration of the vaginal mucosa was detected in all patients of the control group and in 90% of patients in the main group. Repeated examinations 4 months after the end of therapy determined no recurrence of atrophic colpitis in 53.3% of patients in the main group and in 30% of women in the control group. Preservation of a favorable estatrophic type of smears was observed in 43.3% of women of group I and 13.3% of patients of group II (p <0.05), which indicates a more stable effect of hyaluronic acid compared with estrogen-like agent. Conclusions. Vaginal gel with hyaluronic acid Revitaxa gel in women with genitourinary syndrome gives results similar to the synthetic estrogen-like drug with promestrienum for topical treatment according to colposcopy, cytology, hormonal colpocytology and clinical indicators. Therefore, Revitaxa gel may be recommended for effective use in women with atrophic colpitis who refuse or have contraindications for topical hormonal agents.